Relationship Between Age And Work With Nutritional Status Of Wus In Polosari Karangasem Karanganyar Village - Kusudaryati, Dewi Pertiwi Dyah; Noviyanti, Retno Dewi; Innayah, Auliya (Jurnal EduHealth, 2022)
Indonesia experienced burden double problem nutrition that is nutrition not enough Not yet fully overcome , however nutrition more Already showing improvement . Problem nutrition double (double burden) can become problem at all group age Good it's in the village as well as in town . nutrition is one factor decisive importance level health and welfare human. Work and age Also can affect nutritional status . U sia is also related with obesity Where enhancement age cause metabolism body decrease so that happen change biological that is decline function muscle and increased body fat . Data age with nutritional status distributed not normal then using Spearman's Rank tes . Test it used For analyze connection age with WUS nutritional status . Fisher Exact Test used For analyze connection work with the nutritional status of WUS in Polosari Karangasem Karanganyar Hamlet Research This use design cross sectional . Sample in study This is an Aged Woman Subur (WUS) as many as 50 people . Research results This is No There is connection age with WUS nutritional status (p = 0.995) and not There is connection age with WUS nutritional status (p=0.142).